Corporate governance, Islamic governance and earnings management in Oman: A new empirical insights from a behavioural theoretical framework. Issue 2 (2nd May 2017) - Elghuweel, Mohamed I.; Ntim, Collins G.; Opong, Kwaku K.; Avison, Lynn
Abstract : Purpose: The purpose of this paper is to examine the impact of corporate (CG) and Islamic (IG) governance mechanisms on corporate earnings management (EM) behaviour in Oman. Design/methodology/approach: The authors employ one of the largest and extensive data sets to-date on CG, IG and EM in any developing country, consisting of a sample of 116 unique Omani listed corporations from 2001 to 2011 (i.e. 1, 152 firm-year observations) and a broad CG index containing 72 CG provisions. The authors also employ a number of robust econometric models that sufficiently account for alternative CG/EM proxies and potential endogeneities. Findings: First, the authors find that, on average, better-governed corporations tend to engage significantly less in EM than their poorly governed counterparts. Second, the evidence suggests that corporations that depict greater commitment towards incorporating Islamic religious beliefs and values into their operations through the establishment of an IG committee tend to engage significantly less in EM than their counterparts without such a committee. Finally and by contrast, the authors do not find any evidence that board size, audit firm size, the presence of a CG committee and board gender diversity have any significant relationship with the extent of EM. Originality/value: To the best of the authors' knowledge, this is a first empirical attempt at examining the extent to which CG and IG structures may drive EM practices that explicitly seek to draw new insights from a behavioural theoretical framework (i.e. behavioural theory of corporate boards and governance).